Simplified design procedure for controlled spine frames with energy-dissipating members. (August 2017) - Chen, X.; Takeuchi, T.; Matsui, R.
Abstract: A controlled spine frame system consisting of an elastic moment frame, elastic spine frame and concentrated yielding elements is proposed to ensure continuous usability of buildings in the event of an earthquake exceeding the design level. Prior studies have documented the excellent performance of spine frame structures in preventing both the concentration of damage in soft stories as well as in providing self-centering. The current study develops a simplified design method based on equivalent dual multi-degree-of-freedom and single-degree-of-freedom representations, discussing the effects of damper yield drift, and stiffness ratios between the elastic moment frame, spine frame, and dampers on the structural response. This design method is validated with a parametric study and optimal ranges of the stiffness ratios are provided. Highlights: Two simplified models are proposed for the controlled spine frame system. A simple yet very applicable design method is proposed for the system. Seismic performance of the system with various structural parameters is studied. Clear limitations and recommendations for the proposed method are established.